Inequality on the Pacific Northwest Coast of North America measured by house-floor area and storage capacity. (August 2020) - Ames, Kenneth M.; Grier, Colin
Abstract: Abstract : Recent large-scale comparative archaeological studies of wealth differences have used Gini coefficients to assess inequality, employing house-floor area as a standardised, cross-cultural proxy for wealth. Two such studies have found that storage capacity produces higher Gini coefficients than floor area, suggesting that the latter measures household wealth, while the former reflects anticipated income. Here, the authors test these relationships using the floor area and storage capacity of excavated houses on the Lower Columbia River in the Pacific Northwest. The results, which reflect those from previous studies, support the cross-cultural nature of the pattern, and show that storage capacity reflects food-surplus deployment strategies rather than anticipated household income.